2016
DOI: 10.1377/hlthaff.2016.0130
|View full text |Cite
|
Sign up to set email alerts
|

Physician Consolidation: Rapid Movement From Small To Large Group Practices, 2013–15

Abstract: In the past few decades there has been a trend of physicians moving from smaller to larger group practices. We found that this trend continued in the period 2013-15. Primary care physicians have made this change at a much faster pace than specialists have.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 13 publications
2
68
1
Order By: Relevance
“…Compared with vertically integrated organizations, horizontally integrated organizations appeared to more selectively target physicians that had attested to MU. The data therefore do not indicate that horizontal integration provided the potential benefit of EHR adoption and MU attestation, and as others have remarked, horizontal integration can threaten the competitive landscape by consolidating physician market power . Given the selective integration patterns we observed, future efforts and subsidies aiming to accelerate health IT adoption and advancement may need to be better targeted.…”
Section: Discussioncontrasting
confidence: 55%
“…Compared with vertically integrated organizations, horizontally integrated organizations appeared to more selectively target physicians that had attested to MU. The data therefore do not indicate that horizontal integration provided the potential benefit of EHR adoption and MU attestation, and as others have remarked, horizontal integration can threaten the competitive landscape by consolidating physician market power . Given the selective integration patterns we observed, future efforts and subsidies aiming to accelerate health IT adoption and advancement may need to be better targeted.…”
Section: Discussioncontrasting
confidence: 55%
“…In 2015, more than two-thirds of primary care physicians were in groups of 11 clinicians or more. 11 Given that our participating practices represented independent and hospital system practices, as well as federally qualified health centers (FQHCs), we hypothesized that practices would differ by their ownership structure in the degree of clinician and nonclinician burnout, work environment, and psychological safety at baseline.…”
Section: Introductionmentioning
confidence: 99%
“…Medicare, Medicaid, and commercial payers are rapidly adopting ACO contracts. (4, 5) Inpatient spending is an essential focus for cost growth reduction throughout Medicare, and for Medicare ACOs in particular (the Pioneer ACO program, the Medicare Shared Savings Program, and Next Generation ACO Model). This is because inpatient hospital spending accounted for 32% of fee-for-service Medicare spending in 2013.…”
mentioning
confidence: 99%
“…Analysis of savings from the first two performance years of the Pioneer model (2012 and 2013) found that inclusion of a hospital had no effect on whether the ACO had savings or losses(19), but ACOs with hospitals performed better on ACO quality measures than ACOs that did not. (20) While theories about the importance of a hospital to the ACO model have been considered (21), this analysis is the first to assess the actual participation of hospitals in ACOs using a mixed-methods approach. In this paper, we analyze the types of hospitals participating in ACOs to determine whether they differ from those not participating, and analyze advantages and disadvantages to hospital inclusion from an ACO perspective.…”
mentioning
confidence: 99%